The Impact of Capital Adequacy, Financing Risk, and Profitability on the Market Share of Islamic Banks in Indonesia - Murtadho, Taufiq Ridwan; Ponirah, Ade; Hidayat, Nendi Nur; Sakinah, Gina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the effect of the Capital Adequacy Ratio, Net Non-Performing Financing, and Return on Assets on the market share of Islamic Commercial Banks in Indonesia. Market share is measured as the percentage of Islamic Commercial Banks assets relative to total national banking assets. The study employs a quantitative approach using multiple linear regression analysis with quarterly aggregate data of Islamic Commercial Banks from Q1 2010 to Q4 2024. Data were obtained from the Islamic Banking Statistics published by the Financial Services Authority. The results reveal that Capital Adequacy Ratio and Net Non-Performing Financing significantly influence market share, while Return on Assets does not. Simultaneously, the three variables significantly affect market share with a coefficient of determination of 70.4%. These findings highlight that capital adequacy and financing quality are the primary factors driving the competitiveness of BUS, while profitability Return on Assets does not have a direct impact on market share expansion